New Pd and Pt Complexes of Guanine –Azo Dye: Structural, Spectroscopic, Dyeing Performance and Antibacterial Activity Studies - J. Al-Hasani, Thanaa; S. Almaliky, Zainab (Iraqi Journal of Science, 2023)
Four new complexes of Pd(II), Pt(II) and Pt(IV) with DMSO solution of the ligand 8-[(4-nitrophenyl)azo]guanine (L) have been synthesized. Reaction of the ligand with Pd(II) at different pH gave two new complexes, at pH=8, a complex of the formula [Pd(L)2]Cl2.DMSO (1) was formed, while at pH=4.5,the complex[Pd(L)3]Cl2.DMSO (2) was obtained. Meanwhile, the reaction of the ligand with Pt(II) and Pt(IV) revealed new complexes with the formulas[Pt(L)2]Cl2.DMSO (3)and [Pt(L)3]Cl4.DMSO (4) at pH 7.5 and 6 respectively.All the preparations were performed after fixing the optimum pH and concentration. The effect of time on the stability of these complexes was checked. The stoichiometry of the complexes was determined by the mole ratio and Job methods. The complexes were characterized by micro elemental analysis and molar conductivity together with the magnetic susceptibility measurements. Spectrophotometric measurements, UV-Vis, FT-IR and A.A were also performed. 1H NMR spectra for the ligand and [Pd(L)3]Cl2.DMSO complex were also done. A square planar geometry was suggested for complexes (1) and (3), and octahedral structure for complexes (2) and (4).The Dyeing performance and the antibacterial activities for the ligand and its complexes were also tested.